Pengujian Piranti Tempat Sampah Otomatis Berbasis Sistem Tertanam Menggunakan Mikrokontrol Arduino Uno - Fransiska Delsiana; Christy Mahendra; Putu Samuel Prihatmajaya (Politeknik Kampar, 2023)
Trash cans are very important in maintaining the cleanliness and health of the environment, especially in densely populated urban areas. Garbage bins are a necessity for today's society. Currently, technology is developing very rapidly in the development of industrial products, including automatic trash cans. This study aims to create an automatic trash bin based on Arduino Uno and an Ultrasonic Sensor device for object detection, LCD, LED, Speaker, and Servo Motors. The result of this research is an automation system in the form of an automatic trash can system using Arduino Uno. Testing of embedded system input and output devices worked well with tests of up to 40 times with a result of 90%. These results indicate that the embedded system input and output devices for automatic trash bins can function optimally, effectively and efficiently as industrial products.